2018
DOI: 10.1002/adem.201800505
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Model Two‐Phase Composites with Continuous Compared to Discontinuous Phases

Abstract: Composites with stiff and soft phases are widely used in engineering applications and are found in nature. Geometrical arrangements of phases in composites can significantly influence overall properties. This study focuses on the numerical and experimental investigation of the mechanical behavior of model two‐phase composites with different phase geometries including an interpenetrating phase composite with two continuous phases, a matrix‐inclusion composite with a continuous and a discontinuous phase, and a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In all uninfiltrated samples, the porosity guided the crack formation. Similar behavior is seen in many biological materials, including the porcupine fish spine and bone [56]. Cracks travel through porous regions, forming patterns mirroring the alignment of the microstructures formed by lamellae.…”
mentioning
confidence: 64%
“…In all uninfiltrated samples, the porosity guided the crack formation. Similar behavior is seen in many biological materials, including the porcupine fish spine and bone [56]. Cracks travel through porous regions, forming patterns mirroring the alignment of the microstructures formed by lamellae.…”
mentioning
confidence: 64%
“…Besides, spatially resolved nanoindentation measurements allow stiffness mapping and thus locating soft and hard areas across the sample surface. For example, several studies demonstrated that such mechanical heterogeneities in sample surface could result from the presence of areas with different chemical composition or structural features (Liu, et al, 2011;Magonov, et al, 1997;Sabet, et al, 2018). Some authors also evidenced formation of hard/soft regions on the surface of milk powders subjected to long-term storage conditions using this technique Prime, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Developing high‐performance alloys with less or no alloying has been considered as a novel strategy for the sustainable development of materials . By controlling the microstructure morphology and phase distribution, substantial improvements in properties can be achieved without adding an increasing number of elements . One classical example is the gradient nano‐grained materials, which display remarkable enhancements in both strength and ductility .…”
Section: Introductionmentioning
confidence: 99%